Problematika siswa siswi: Pembelajaran bahasa Arab di sekolah umum dan upaya penyelesaiannya - Hotimah, Khusnul (Maliki Interdisciplinary Journal, 2024)
Language is an important communication tool to be able to interact with other people. With language, humans can express their messages, desires, and ideas well so that they can be understood by other humans. Because the many languages that exist in this world can be different from other parts of the world, good learning is needed so that the language can be learned by other humans. Including one of the languages that Muslims must learn, namely Arabic. This language must be learned by a Muslim or Muslimah, because it is the language of Islamic religion itself. the type of research used in this article is descriptive qualitative with a library research method approach. The data collection technique is by documentation from journals published during the last five years with the theme of student problems, linguistic and non-linguistic. Problems in learning Arabic include linguistic (language) and nonlinguistic (not language). Linguistic problems include language structure, vocabulary, phonetics, writing, and others. While nonlinguistic problems include child psychology, learning time, learning tools or facilities, teaching and learning methods, and the surrounding environment. The problems that occur are very complex depending on the maturity of learning and the surrounding environment. This article tries to reveal solutions to Arabic language learning problems in a public school environment.